IMMUNE STATUS OF CHILDREN WITH ASTHMA AT PERSISTATION OF CHLAMYDIA PNEUMONIA - D.I. Novosad; N.G. Bychkova; M.P. Prokhorova; M.V. Khaytovych (Bogomolets National Medical University, 2016)
We studied the immune status of children of different age groups with asthma of moderate severity in a stage of remission. It was revealed that the changes in cellular immunity (reduction of the number of leukocytes and absolute counts of lymphocytes, reduction of absolute amount of CD3 + lymphocytes, CD4 + lymphocytes, CD8 + lymphocytes, B-lymphocytes and natural killer cells, decreased functional activity of T-lymphocytes and phagocytic activity of neutrophils) were more pronounced with presence of high titer of specific IgG- and IgM- antibodies to Chlamydia pneumonia. After the study of humoral immunity in children with asthma in a stage of remission with presence of specific IgG- and IgM-antibody to Cl.pneumonia we found that there is reduced amount of large molecular circulating immune complexes with a constant of sedimentation >19S and elevated levels of highly pathogenic small and medium molecular circulating immune complexes. Increased concentration of pathogenic circulating immune complexes in children with asthma in a stage of remission is also accompanied in older children with defection of metabolic activity of neutrophils and elimination of circulating immune complexes from the body. Thus, changes in the immune system of children with asthma and persistence of Cl.pneumonia extend to all parts of the immune system and have symptoms of secondary immunodeficiency, which requires application of immunotherapy, adaptogenic and sorption therapy. In addition, a significant proportion of children has persistent herpesvirus (Cytomegalovirus, Epstein-Barr virus, herpes simplex virus type I-II) and intracellular (Cl. Pneumoniae, Mycoplasma pneumoniae) infection, including the mixed infection. Therefore, it is crucial to identify and control it in order to prevent recurrence of asthma in this group of children.